Assessment of Three Therapeutic Procedures in the Prevention of Diabetic Macular Oedema after Phacoemulsification through Intraocular Lens Implementation (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
A cataract is an ocular complication of diabetes mellitus, and the risk of developing diabetic macular oedema (DME) increases in cataract surgery. This randomized, single-blind clinical trial study was conducted on 45 eyes (39 patients) with stable diabetic retinopathy with cataract to compare the efficacy of three therapeutic procedures in the prevention of DME after phacoemulsification through intraocular lens implantation. After cataract surgery by phacoemulsification, the patients were randomly assigned into three groups. The group A received 1.25 mg of intravitreal bevacizumab, and group B received a sub-tenon injection of 40 mg triamcinolone at the end of the surgery. The group C received topical diclofenac drops every 8h for four weeks after the surgery. Results showed there was no significant difference in the demographics and clinical features, central macular thickness, and systemic condition of the three groups at the beginning of the study. There was a significant difference between the preoperative and postoperative periods (i.e., three months after surgery) in the three groups regarding mean macular thickness; however, the difference among the three groups was not significant in the post-operative periods. The DME after cataract surgery occurred in 4 eyes (26.67%) in the diclofenac group and three eyes (20.00%) in the intravitreal bevacizumab and three eyes (20.00%) in sub-tenon triamcinolone groups. According to results, the administration of these three therapeutic procedures can be beneficial in the prevention of DME in patients with cataract and diabetic retinopathy.